2021
DOI: 10.1177/09645284211017303
|View full text |Cite
|
Sign up to set email alerts
|

Acupuncture for chronic pain in adults with sickle cell disease: a mixed-methods pilot study

Abstract: Objective: Chronic pain is a common symptom experienced among patients with sickle cell disease (SCD). Our aims were to assess the feasibility and acceptability of performing acupuncture for the treatment of chronic pain in adults with SCD. Methods: This was a single-arm, prospective pilot study of six adults with SCD. Participants reported ⩾ 3 months of chronic pain and were > 18 years of age. Per protocol, acupuncture was to be administered twice per week for 5 weeks, for 30 min per session. All treatment… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 34 publications
1
5
0
1
Order By: Relevance
“…All participants will be scheduled to complete assessments at 4 time points: baseline (at study enrollment), week 6 (midpoint), week 12 (intervention end), and week 24 (follow-up). The rationale for the 6-week assessment time point is based on our clinical knowledge and our pilot studies [ 15 , 39 ], which have shown positive effects of CIH therapies after 5 weeks of intervention.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…All participants will be scheduled to complete assessments at 4 time points: baseline (at study enrollment), week 6 (midpoint), week 12 (intervention end), and week 24 (follow-up). The rationale for the 6-week assessment time point is based on our clinical knowledge and our pilot studies [ 15 , 39 ], which have shown positive effects of CIH therapies after 5 weeks of intervention.…”
Section: Methodsmentioning
confidence: 99%
“…Since many people with SCD try 2 or more therapies, there is a need to rigorously test the effects of adding a subsequent therapy when the first does not produce the desired outcomes within a given time period. The Hybrid Effectiveness-implementation Trial of Guided Relaxation and Acupuncture for Chronic Sickle Cell Disease Pain (GRACE) is assessing the outcomes of sequencing 2 evidence-based CIH therapies [ 15 , 16 ], acupuncture and guided relaxation, among SCD patients with chronic pain who are being treated in real-world health care systems.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Students shared information about many additional clinically relevant topics during our course discussions, such as circadian rhythm and sleep disorders (e.g., shift-work sleep disorder, narcolepsy, and sleep apnea) and the efects of hypnotic and stimulant drugs. We also provided exposure to relevant faculty research activities; for example, one faculty member (JMS) is a nurse scientist and a licensed acupuncturist, and her team's research illustrated how acupuncture can be used to manage pain and cardiovascular disorders, according to its efects on the ANS [10][11][12]. Other faculty members with active research programs incorporated examples from their relevant work about neuroscience (MWC and AMF; [13,14]), stroke (SRM; [15]), diabetes (CF and LQ; [16]), and the microbiome (MBL; [17]).…”
Section: Receptors and Ligandsmentioning
confidence: 99%
“…Atualmente os opioides são uma forma comum de controle da dor na doença falciforme, mas que está associada a múltiplos efeitos colaterais e dependência, o que inspira novas formas de analgesia nesses pacientes. Nesse sentido, em estudo piloto recente, a realização de acupuntura por 5 semanas se mostrou viável e aceitável para tratamento da dor crônica em adultos com doença falciforme, mas que é preciso um estudo controlado randomizado maior para avaliar os efeitos da acupuntura (Li et al, 2021).…”
Section: Acupuntura Na Dor Crônica Da Doença Falciformeunclassified